2022
DOI: 10.3390/pharmaceutics14030545
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Sialic Acid and PEG Modified Epirubicin Liposomes in Aged versus Young Cells and Tumor Mice Models

Abstract: In preclinical studies of young mice, nanoparticles showed excellent anti-tumor therapeutic effects by harnessing Peripheral Blood Monocytes (PBMs) and evading the immune system. However, the changes of age will inevitably affect PBMs and the immune system, and there is a serious lack of relevant research. Sialic acid (SA)-octadecylamine (ODA) was synthesized, and SA- or polyethylene glycol (PEG)-modified epirubicin (EPI) liposomes (EPI-SL and EPI-PL, respectively) were prepared to explore differences in antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The DiR-SAPLs mainly target TAMs in the tumor periphery microenvironment; therefore, the tumor collection procedure involves separating the tumor from the surrounding environment (where numerous TAMs are concentrated with high fluorescence signal), leading to lower fluorescence signal at the tumor area and resulting in no significant difference in fluorescence intensity compared with the DiR-PL liposome group in ex vivo images. Sui et al also found no statistically significant difference between the tumor DiR fluorescence intensity for PEGylated liposomes and SAmodified liposomes [79].…”
Section: In Vivo Biodistributionmentioning
confidence: 94%
“…The DiR-SAPLs mainly target TAMs in the tumor periphery microenvironment; therefore, the tumor collection procedure involves separating the tumor from the surrounding environment (where numerous TAMs are concentrated with high fluorescence signal), leading to lower fluorescence signal at the tumor area and resulting in no significant difference in fluorescence intensity compared with the DiR-PL liposome group in ex vivo images. Sui et al also found no statistically significant difference between the tumor DiR fluorescence intensity for PEGylated liposomes and SAmodified liposomes [79].…”
Section: In Vivo Biodistributionmentioning
confidence: 94%
“…The phenomenon of tumor shedding has also been reported in the previous studies. 19,[57][58][59] We attempt to explain the mechanism by which the tumors were shed with a hypothesis focusing on the microtubulin. To begin with, the first step in co-administration is the intravenous administration of PTX cationic liposomes.…”
Section: In Vivo Antitumor Activitymentioning
confidence: 99%
“…A modified ethanol injection method was used to prepare liposomes. 42 The DSPE-mPEG 1,2K , CH, DOTAP, and PC-98T (6:1:3:15, m/m/m/m) were dissolved using absolute ethyl alcohol, and ICG was dissolved in water (ICG/DOTAP ). After a 4 h incubation, the medium containing PEGylated cationic liposomes was added.…”
Section: Preparation Of the Liposomesmentioning
confidence: 99%
“…A modified ethanol injection method was used to prepare liposomes. 42 The DSPE-mPEG 1,2K , CH, DOTAP, and PC-98T (6:1:3:15, m/m/m/m) were dissolved using absolute ethyl alcohol, and ICG was dissolved in water (ICG/DOTAP = 2:3, m/m). After the ethanol was dried at 50 °C, the ICG solution was added to the phospholipid material and stirred for 20 min to produce the prime liposomes.…”
Section: Preparation Of the Liposomesmentioning
confidence: 99%